Stiripentol for the treatment of super‐refractory status epilepticus with cross‐sensitivity. (3rd January 2018) - Uchida, Y.; Terada, K.; Madokoro, Y.; Fujioka, T.; Mizuno, M.; Toyoda, T.; Kato, D.; Matsukawa, N.
Abstract : Background: Cross‐sensitivity of rash has been reported between various antiepileptic drugs (AEDs). However, few studies have determined the frequency and management of cross‐sensitivity in patients with super‐refractory status epilepticus (SRSE). Aims of the study: To examine the optimal AED for treating SRSE with cross‐sensitivity. Methods: We performed a retrospective review of adult patients with SRSE treated at Nagoya City University Hospital, in which we investigated the frequency of cross‐sensitivity among patients with SRSE and their clinical and medical profiles. Results: We identified 10 adult patients with SRSE, 5 of whom had cross‐sensitivity. Stiripentol (STP) was administered when previously used AEDs had demonstrated cross‐sensitivity and failed to control seizures. After initiation of STP, the dose of general anaesthetics was reduced, and status epilepticus (SE) eventually ceased with co‐administered AEDs without additional adverse effects. The mean time to SE cessation after initiation of STP was 30.8 days (range, 18‐46 days), mean duration of general anaesthesia was 101.2 days (range, 74‐128 days), and mean number of AEDs was 9.0 (range, 6‐11). Conclusions: This study suggests that cross‐sensitivity between AEDs is common in adults with SRSE and that STP may be useful for treating SRSE with cross‐sensitivity.